Impact of Aspirin Supplementation for Pre-Eclampsia Prevention on Neonatal Outcomes - Campo, Bertha; Fogel, Joshua; Na, Sean; Bryson, Lennox (Kansas Journal of Medicine, 2023)
Introduction. Preeclampsia affects approximately 4.6% of pregnancies worldwide. In 2018, ACOG updated their low dose aspirin (LDA) supplementation recommendation to include pregnant women at moderate risk for preeclampsia. In addition to the potential benefit of LDA supplementation for delaying or preventing preeclampsia, LDA supplementation can affect neonatal outcomes. We study the association of LDA supplementation with six neonatal outcomes: length of stay (LOS) in hospital, NICU admission, hospital readmission, birth weight (BW), one-minute Apgar score, and five-minute Apgar score in a sample of mostly minority pregnant women from Hispanic and Black race/ethnicities. Methods. This was a retrospective study of 634 patients from January 2018 through April 2021.Our main predictor variable was maternal LDA supplementation on 6 neonatal outcomes: NICU admission, neonatal readmission, one and five minute Apgar scores, neonatal BW and hospital LOS. We adjusted for demographics, comorbidities and maternal high- or moderate-risk designation per ACOG guidelines. Results. We found that high-risk designation was associated with neonatal increased rate of NICU admission (OR: 3.80, 95% CI: 2.02, 7.13, p<0.001), LOS (B=0.15, SE=0.04, p<0.001) and decreased birthweight (B=-442.10, SE=75.07, p <0.001). We found no significant association with LDA supplementation and NICU admission, readmission, low one and five minute Apgar scores, BW and LOS. Conclusions. We did not find any association of LDA supplementation with NICU admission, hospital readmission, low one-minute or five-minute Apgar score, birthweight, and LOS. Clinicians recommending maternal LDA supplementation should be aware that LDA supplementation does not appear to provide any benefits for these neonatal outcomes.